Comparison of the accuracy and the response time to behavioral pain scales (BPS and CPOT) during painful procedures in the intensive care unit - Ladan Sedighi; Shima Shirozhan; Elaheh Talebi-Ghane; Abbas Taher; Ensieh Eliasi; Razieh Gomar; Zhale Mollai (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Pain is one of the most common symptoms in the patients hospitalized in intensive care units, and its correct and timely diagnosis is important. Identifying tools that accurately assess pain in a shorter time will help patients better manage pain. The aim of this study was to compare the accuracy and the duration of response to behavioral pain scales (BPS and CPOT) during painful procedures in the intensive care unit. MATERIALS AND METHODS: The descriptive-comparative study was conducted in two groups, each including 16 nurses, in the intensive care unit of Besat Hospital in Hamadan in 2022. Each group separately evaluated the patients' pain during position change and secretion suction based on BPS and CPOT scales along with an evaluator. At the same time, the accuracy of the scores given by each nurse and the duration of pain diagnosis were compared using the determined evaluator, and the results were analysed. RESULTS: Comparing the durations of response to the scales, the average duration of response for BPS and CPOT tools were 13.21 and 13.63, respectively; in general, their difference was significant (P < 0.001). Examining the accuracy of the nurses and the evaluators in pain evaluation revealed a significant difference between the two tools, and the results of adaptability were higher for CPOT, in all cases, in comparison with BPS (P = 0.024). CONCLUSIONS: The results showed that CPOT assesses the pain more accurately compared to BPS, but the duration of pain evaluation is a little longer via CPOT. The results of the study can help the nurses working in ICUs by choosing more accurate tools with shorter evaluation duration.